Hadiths on Thalaq and Iddah with Psychological and Theological Normative Approaches - Samsuri (Jurnal Hukum Keluarga, 2024)
Divorce (talaq) and the iddah period are two very important concepts in Islamic law, with both having a profound impact both theologically and psychologically. The Hadiths governing talaq teach that while divorce is permissible in Islam, it is a step that is hated by Allah and should only be done in very urgent situations, after various attempts to repair the relationship have failed. Likewise, the iddah period, which is obligatory for women who are divorced or whose husbands die, has many wisdoms, including providing an opportunity women to self-reflect and ensure their honor and pregnancy status. This paper aims to analyze the normative theological and psychological dimensions of thalaq and iddah. The normative theological approach discusses the Islamic legal basis for divorce and iddah, the wisdom behind their implementation, and the principles of justice and compassion contained in these teachings. Meanwhile, the psychological approach explores the emotional impact experienced by individuals, including husbands, wives, and children, in the face of divorce. The emotional recovery process required, as well as the importance of social and spiritual support during the iddah period, are also discussed in this article. As such, this article not only provides an understanding of the laws of thalaq and iddah in Islam, but also highlights the importance of emotional and psychological well-being for individuals involved in the divorce process and the iddah period.